Seagrass Community Structure in the Coastal Waters of Pandanan Sekotong Barat, West Lombok - Suryatni, Maulida; Santoso, Didik; Japa, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Seagrass ecosystems play a crucial role in marine environments, particularly in supporting coastal biodiversity and maintaining ecological balance. The coastal waters of Pandanan Beach are ecologically vital but potentially exposed to anthropogenic pressures such as boat mooring and local foraging (